2021
DOI: 10.1186/s12920-021-01010-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of macrophage related gene in colorectal cancer patients and their functional roles

Abstract: Background Recent scientific research has enabled the identification of macrophages related-genes (MaRG), which play a key role in the control of the immune microenvironment in many human cancers. However, the functional role of MaRGs in human tumors is ill-defined. Herein, we aimed at bioinformatically exploring the molecular signatures of MaRGs in colorectal cancer. Methods A list of MaRGs was generated and their differential expression was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“… 32 The PRC1 has also been identified as one of the hub macrophage‐related genes in colorectal cancer patients. 33 As for BIRC5, similarly, it is reportedly expressed at particularly high levels in prostate tumors characterized by infiltration of TAMs, suggesting its potential correlation with TAM infiltration. 18 We therefore wondered whether PRC1 and BIRC5 participate in the maintenance of M2 TAMs in the TME of NPC as well.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“… 32 The PRC1 has also been identified as one of the hub macrophage‐related genes in colorectal cancer patients. 33 As for BIRC5, similarly, it is reportedly expressed at particularly high levels in prostate tumors characterized by infiltration of TAMs, suggesting its potential correlation with TAM infiltration. 18 We therefore wondered whether PRC1 and BIRC5 participate in the maintenance of M2 TAMs in the TME of NPC as well.…”
Section: Discussionmentioning
confidence: 88%
“…In hepatocellular carcinoma, likewise, high PRC1 expression has been linked to increased TAM infiltration and poor prognosis of patients 32 . The PRC1 has also been identified as one of the hub macrophage‐related genes in colorectal cancer patients 33 . As for BIRC5, similarly, it is reportedly expressed at particularly high levels in prostate tumors characterized by infiltration of TAMs, suggesting its potential correlation with TAM infiltration 18 .…”
Section: Discussionmentioning
confidence: 98%
“…NIT2 , identified as ω-amidase, plays an important metabolic role by catalyzing hydrolysis of α-ketoglutaramate and α-ketosuccinamate, yielding α-ketoglutarate and oxaloacetate, respectively 18 , 19 . Some studies have shown that the overexpression of NIT2 is related to the occurrence and development of colon cancer 20 , 21 and tongue squamous cell carcinoma 22 . In colon cancer, the downregulation of NIT2 inhibits the proliferation of colon cancer cells and induces cell cycle arrest through the caspase-3 and PARP pathways.…”
Section: Discussionmentioning
confidence: 99%